Gram‐Scale Synthesized Two‐Dimensional VSe2 and SnSe2 for Ultrahigh Electrocatalytic Sulfion Recycling. Issue 13 (7th April 2022) - Feng, Wang; Cheng, Mo; Du, Ruofan; Wang, Yuzhu; Wang, Peng; Li, Hui; Song, Luying; Wen, Xia; Yang, Junbo; Li, Xiaohui; He, Jun; Shi, Jianping
Abstract: The electrocatalytic sulfion (S 2− ) recycling and hydrogen (H2 ) evolution play indispensable roles in converting waste into sustainable energy and boosting hydrogen economy. However, the development of such promising technologies is hindered by the lack of electrocatalysts with low‐cost, high‐efficient, and robust stability. 2D VSe2 and SnSe2 hold great application potentials in the energy‐related fields yet face daunting challenges in terms of large‐scale synthesis. Herein, a gram‐scale and high‐yield strategy is designed with tetradecylamine (TDA) assistance for synthesizing 2D VSe2 and SnSe2 . The cooperativity of TDA with V 4+ (Sn 4+ ) cations and its stabilization to (100) facets of products contribute to the formation of ultrathin VSe2 nanosheets with abundant wrinkles and SnSe2 nanoflowers with hierarchical structures, which deliver excellent hydrogen evolution reaction and oxygen evolution reaction performances. Significantly, a record‐breaking sulfion oxidation reaction efficiency in 2D VSe2 is uncovered, and the current density is one order of magnitude larger than that of commercial Pt/C catalyst. This work presents a significant breakthrough for scalable synthesize 2D electrocatalysts and provides a new paradigm for sustainable hydrogen generation and water purification. Abstract : A gram‐scale strategy is designed for synthesizing 2D VSe2 and SnSe2 . The ultrathin VSe2 nanosheets with abundant wrinkles and SnSe2 nanoflowers with hierarchical structures deliver excellent electrocatalytic performances. Significantly, a record‐breaking sulfion oxidation reaction efficiency is uncovered in 2D VSe2, and the current density is one order of magnitude larger than that of commercial Pt/C catalyst.